The Development Of Women's Participation In Political Life - Azima Dimyati (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The formation of culture unilaterally by men causes the women marginal in politics, economics and culture. Women in the position of the other impacting against the subsequent displacement of many women in the structure of male dominance. Global democracy movement must go through an equivalent political system setup, evoking a fair representation of the political system. The Reformation restores the natural of women as subjects of political, social and economics level with men. It Needs to design strategic programs to struggle the empowerment of women in the entire field of social life. Women's participation in  attitude, ability, knowledge, in terms of institutional management, strengthening the network coordinating goals already planned. Realizing gender equality and justice in the political sphere, women have access, the same rights and responsibilities with men. The most appropriate strategy is affirmative action that can develop actions the leadership and political participation of women in the legislature, Executive, and judicial. The problems faced by women to become a leader comes from the women's own internal and external. Until the 2014 election, the newly implementation legislative candidate for women also haven’t met the quota of 30%, accordingly mandated by law.